Textured propyl gallate modified MXene biopaster with prolonged photothermal effect for in-situ post-surgery residual tumor clearance. (February 2023) - Wang, Xiang; Sun, Feifei; Wang, Ya; Yan, Zidi; Wang, Xunrui; Kong, Haoran; Wang, Yu
Abstract: Residual tumors after surgery lead to a high risk of recurrence, and effective strategies clearing the residual tumors urgently need to be developed. Locally administering antitumor agents after surgery has been proved effective to clear residual tumor cells, but achieving long-lasting efficacy and repeatable treatment are still challenges for these agents. In this study, we orderly arranged propyl gallate (PG)-grafting MXene onto calcium-alginate hydrogel (CA) layer to develop a photothermal-responsive biopaster for the tumor post-surgery recurrence prevention. The order arrangement of PG-grafting MXene nanosheets with the prolonged degradation time (compared to the non-PG-grafting ones) could retain the photothermal responsiveness for 14 days. Therefore, this biopaster provided long-term photothermal therapeutic capability to kill the residual tumors and effectively prevented the tumor recurrence (after surgery). This work provides references for designing NIR-responsive 2D nanomaterials with enhanced NIR-responsiveness and long-term antitumor efficacy. Graphical Abstract: A bilayered biopaster (TLM-CA) consisting of textured propyl gallate (PG)-grafting MXene responsor and calcium alginate (CA) adhesive supporting is designed for in-situ post-surgery residual tumor clearance under NIR irradiation. The key order arrangement of PG-grafting MXene nanosheets accelerates the light-heat conversion and prolonged the repeatable photothermal effect over 14 days. The flexible TLM-CA biopaster with tailored coverage provides a rapid and long-term photothermal efficacy for postoperative residual tumor ablation. ga1 Highlights: Oxidative degradation against MXene-PG for improving photothermal efficiency and long-term stability. Textured MXene-PG nanosheets accelerates the photothermal responsiveness and prolongs the photothermal effect. Film-like biopaster can eradicate residual tumor cells spreading over distant tissues through photothermal ablation. TLM-CA biopaster provides references for designing PTT nanomaterials with enhanced and prolonged antitumor efficacy.